RETRACTED: Analysis of the effectiveness of using torsional vibration dampers for crankshafts with adaptive characteristics in internal combustion engines - Khaliullin Farit; Latipov Ravil; Khaliullina Zulfiya; Gurgenidze Zurab; Vakhrameev Dmitry; Potapov Evgeniy (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001